PERAN DINAS PERTANIAN DALAM MENINGKATKAN PENDAPATAN PETANI MENURUT PERSPEKTIF EKONOMI ISLAM - Elvira Maisandra; Ariyun Anisah (CV. Adiba Aisha Amira, 2023)
The background of this research is because the problems of farmers in Jorong Piladang are still practicing traditional farming, then farmers also lack access to subsidized fertilizers and farmers who have not been able to process their crops into raw materials ready for sale. The purpose of this study is to determine the role of the Department of Agriculture in Increasing Farmers' Income According to the Perspective of Islamic Economics. This research is a field research using a qualitative descriptive approach. The data were collected using observation techniques, interviews, documentation and literature studies. The data that has been obtained is then analyzed following the stages of data reduction, data presentation, and drawing conclusions and verification. The results of this study indicate that the Department of Agriculture plays an important role in increasing farmers' income. There are 3 roles of the Department of Agriculture which are in line with the expectations of the Farmers including an active role such as the Department of Agriculture which has provided counseling to farmers through PPL regularly in a month at least once. The participatory role can be seen that the Agriculture Office provides programs to extension workers so that they are experts in agriculture. Passive role can be seen that the Department of Agriculture provides assistance to farmer groups in Jorong Piladang. From these three roles, farmers through farmer groups in Jorong Piladang can benefit from the three roles of the Agriculture Service described above.